Fuzzy logic controller of photovoltaic panel-unified power quality conditioner with voltage compensation and stability - Mahmoud Mostefa Tounsi; Bouziane Meliani; Noreddine Benaired; Fatiha Djaafar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
The intensive use of non-linear loads is further contributing in the increase of power quality problems. They cause voltage distortions and current harmonics in an electrical distribution network. To minimize these problems, the unified power quality conditioner (UPQC) is used. The intermediate circuit voltage of this filter can deviate from its source during a transient event during a harmonic disturbance in voltage (voltage dip) or in current during the connection and disconnection of polluting loads. In a particular point in operating time, the stabilization of dc-bus and the compensation ability is necessary to maintain around its reference. The combination of a UPQC conditioner with a photovoltaic (PV) system connected to the intermediate element of the two converters of the DC bus (DC Link) is the adequate solution. The photovoltaic (PV) system is fitted with a fuzzy MPPT controller regulated by an algorithm (P and O) to control a boost converter. This converter is controlled by fuzzy logic related to the capacitor terminal of UPQC. The simulation results show that the UPQC conditioner based on the proposed photovoltaic system can be used for voltage disturbance compensation and the protection of non-linear loads connected to a distribution network.